Antinomi Penerapan Presidential Threshold Dalam Sistem Pemilu Presiden dan Wakil Presiden - Syaiful, M (Jurnal Litigasi Amsir, 2022)
General elections are the most important institution for the fulfillment of the three basic principles of democracy in a government in the form of a republic, namely, people’s sovereignty, the legitimacy of government, and regular changes of government. After going through a long journey, setting the limits for the candidacy of the president and vice president has now been stipulated in Article 222 of Law Number 7 of 2017, this limit setting for the candidacy will apply in the Indonesian presidential and vice-presidential election system, but whether with the existence of the law won’t cause problems later on? This is also related to what the Presidential Threshold means, and its regulation in laws and regulations. What are the pros and cons of the current Presidential Threshold system? This study aims to understand the effect of the use of gadgets on the fulfillment of children’s rights to growth, development, and play. The research method used in this study is a normative approach supported by various library materials, such as reading literature in the form of philosophy books, philosophy journals, online articles, media, and papers. Studies focus more on comparative studies by prioritizing the dialectical process. In addition, the discussion in this article will be arranged systematically, in line with general scientific norms. The presidential threshold setting based on the General election Law has ineffectiveness which contains pros and cons in its implementation, especially in simultaneous general elections. This ineffectiveness is due to namely: contradictions with the amendments to the 1945 Constitution, the injustice of new political parties for general election participants, and the weakening of the presidential system in Indonesia. Based on this, it is necessary to abolish Article 222 of Law Number 7 of 2017 so that implementation follows the principles of a democratic country.